Quantification of emission estimates of CO2, CH4 and CO for East Asia derived from atmospheric radon-222 measurements over the western North Pacific - A. Wada; H. Matsueda; S. Murayama; S. Taguchi; S. Hirao; H. Yamazawa; J. Moriizumi; K. Tsuboi; Y. Niwa; Y. Sawa (Tellus: Series B, Chemical and Physical Meteorology, 2013)
Emissions of CO, CH4 and CO2 in East Asia were estimated using the atmospheric concentration of 222Rn measured at Minamitorishima (MNM) and Yonagunijima (YON) with a high-precision 222Rn measuring system. The 222Rn measurements showed a distinct seasonal variation, as well as enhanced 222Rn (ERN) events associated with high-frequency synoptic variations. The enhancements of CO, CH4 and CO2 coincided with the ERN events at MNM and YON. The enhancement ratios ΔCH4/ΔRn, ΔCO2/ΔRn and ΔCO/ΔRn calculated for the ERN events and corrected for the radioactive decay of 222Rn during the transport were used to estimate the emissions of CO, CH4 and CO2 by multiplying a constant 222Rn exhalation rate of 1.0 atom cm−2 s−1 and the associated catchment area estimated by a 3D transport model. By modifying the categorisation of the sources, the 222Rn-derived emissions of CO2 and CH4 were found to be in agreement with the published emission databases. As for the CO emission, results of our study were consistent with the REAS CO emission database but showed that the EDGAR database underestimates the CO emission over East Asia by about 44%. It is demonstrated that the 222Rn tracer method used in this study could provide a useful and independent tool to verify the trace gas emissions in East Asia.